The relationship between perfectionism and psychological well-being: the mediating role of mindsets - R. Firmalo, Cassandra Sofia; Malcampo, Marie Chiela (Psychology, Society & Education, 2026)
This study explores the relationship between perfectionism dimensions: perfectionistic concerns and perfectionistic strivings, as well as psychological well-being, with mindset as a mediating factor. Perfectionistic concerns are typically linked to maladaptive outcomes, while perfectionistic strivings are associated with positive psychological functioning. A total of 323 Filipino undergraduates (74.9% female) participated in this correlational research. In analyzing the results, Structural Equation Modeling with mediation analysis was employed. Findings from the study showed that perfectionistic concerns was not significantly related to fixed mindset but was negatively related to some aspects of well-being, particularly environmental mastery, purpose in life, and self-acceptance. In contrast, perfectionistic strivings was positively associated with growth mindset and is related to higher levels of autonomy, personal growth, positive relationships, and self-acceptance. Mediation analysis revealed that individuals with a growth mindset tended to exhibit high perfectionistic strivings, leading to enhanced well-being. Both growth and fixed mindsets predicted certain well-being components, suggesting that a fixed mindset may not be entirely harmful. This study highlights the role of mindset in the relationship between perfectionism, particularly perfectionistic strivings, and students’ psychological well-being and functioning, with implications for the development of mindset-based interventions.